ROCED: Robot card biology education as a media for biology learning - Solihin, Solihin; Apriliani, Adelia Siti Nur; Nabila Nur Jannah, An (STKIP Persada Khatulistiwa Sintang, 2025)
The use of innovative and interactive learning media, such as robotics, is essential to increase learning achievement in Biology subjects. This study aims to develop ROCED robotic learning media in biology subjects. The method used is R&D. However, this study is limited to the development stage. This study involved four candidates, consisting of 2 biology teachers, 1 material expert, and 1 informatics expert. A total of 14 vocational high school students were involved in providing responses related to the use of ROCED media. Qualitative data were collected through questionnaire interviews and documentation studies. Quantitative data were analyzed using a validity test. The results of the study showed that the ROCED robotic learning media were feasible to use in the biology learning process. In terms of material, it had a score of 85%, in terms of language, it had a score of 86.6%, the robot design had a score of 88.3%, and in terms of durability, it was 86%. The results of the media feasibility test showed a score between 80% and 93.33%, which indicates that this media is practical to use to support interactive learning and is liked by students.